Bullying Prevention Education for Elementary School-Age Children - Niken Yuniar Sari; Fani Hidayah Putri; Ilya Fitriani; Gustianur Efendi; Nurul Lailatul Jannah; Nofita Septiani; Rizka Amanda Sari; Roswanda Moerza; Salinabela Hartati; Sayang Maulad Tika; Nuraini, Nuraini (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Bullying in school environments is a serious issue frequently faced by adolescents, negatively impacting students' social and emotional development. This community service was conducted at SD Negeri 46 Pekanbaru to identify bullying issues and provide education on bullying prevention to students. The methods used included surveys, interviews, observations, and educational activities with lectures and animated video presentations. Pre-tests and post-tests were administered before and after the educational activities to measure the students' increased knowledge about bullying. The results indicated a significant improvement in students' understanding, with an average pre-test score of 70 increasing to 90.5 in the post-test. This educational intervention successfully raised students' awareness of bullying and prevention steps, creating a safer and more conducive learning environment.